Preconditioning of mesenchymal stem cells with low-intensity ultrasound for cartilage formation in vivo - Cui, Ji Hao; Park, So Ra; Park, Kwideok; Choi, Byung Hyune; Min, Byoung-Hyun (MARY ANN LIEBERT, INC, 2007)
The purpose of this study was to evaluate the benefits of in vitro preconditioning of mesenchymal stem cells (MSCs) using low-intensity ultrasound (US) in the induction of chondrogenic differentiation of MSCs in vivo. After rabbit bone marrow-derived MSCs were seeded onto a polyglycolic acid (PGA) scaffold, the PGA-MSCs constructs were divided into 4 subgroups: untreated control, low-intensity US group, transforming growth factor-beta [TGF]-treated group and low-intensity US/TGF group. The chondrocyte-seeded PGA construct served as a positive control. For 1 week before implantation, the low-intensity US groups were subjected to ultrasound treatment for 20 min daily at an intensity of 200 mW/cm(2). The TGF groups were treated with 10 ng/mL TGF-beta 1. The cells were then implanted into the nude mouse subcutaneously. Retrieved 1, 2, 4, and 6 weeks after implantation, each construct underwent gross examination, histology, biochemical assays, mechanical testing, and reverse transcriptase polymerase chain reaction (RT-PCR). Substantial size reduction and blood invasion were found much earlier in the groups that did not undergo low-intensity US than in those that did. Safranin O/Fast green staining revealed that the chondrogenic differentiation of MSCs was more widespread throughout the constructs in the low-intensity US groups. In the biochemical and mechanical analyses, the low-intensity US and low-intensity US/TGF groups were significantly better in forming hyaline cartilage-like tissue by 4 weeks than the non-low-intensity US groups. Presented by von Kossa staining, the development of osteogenic phenotypes was highly suppressed until 4 weeks in the low-intensity US groups, along with compressive strength comparable to the positive control. In the RT-PCR analysis before implantation, the messenger RNA levels of Sox-9, aggrecan, and tissue inhibitors of metalloproteinase-2 were higher in the low-intensity US groups, while those of type I and type X collagens and matrix metalloproteinase-13 were higher in the non-low-intensity US groups. Blood invasion into the constructs was also considerably hindered in the low-intensity US groups. These results strongly indicate that low-intensity US preconditioning in vitro could be an effective cue to upregulate chondrogenic differentiation of MSCs in vivo.
Keywords: AGGRECAN GENE-EXPRESSION; BONE-MARROW; CHONDROGENIC DIFFERENTIATION; CHONDROCYTE DIFFERENTIATION; ARTICULAR CHONDROCYTES; PROGENITOR CELLS; ANGIOGENESIS; VITRO; OSTEOARTHRITIS; STIMULATION